Investigation of properties of the statistics used to assess the reliability - Єгоров, С.В. (Proceedings of National Aviation University (archive), 2007)
Modeling by a method of Monte Carlo casual samples from general set is lead with the purpose of definition of probability of non-failure operation. The analysis of quality of statistics of a kind is lead.